Prospective longitudinal evaluation of hospitalised COVID-19 survivors 3 and 12 months after discharge. Issue 2 (11th April 2022) - Lorent, Natalie; Vande Weygaerde, Yannick; Claeys, Eveline; Guler Caamano Fajardo, Ipek; De Vos, Nicolas; De Wever, Walter; Salhi, Bihiyga; Gyselinck, Iwein; Bosteels, Cedric; Lambrecht, Bart N.; Everaerts, Stephanie; Verschraegen, Sven; et al.
Background: Long-term outcome data of coronavirus disease 2019 (COVID-19) survivors are needed to understand their recovery trajectory and additional care needs. Methods: A prospective observational multicentre cohort study was carried out of adults hospitalised with COVID-19 from March through May 2020. Workup at 3 and 12 months following admission consisted of clinical review, pulmonary function testing, 6-min walk distance (6MWD), muscle strength, chest computed tomography (CT) and quality of life questionnaires. We evaluated factors correlating with recovery by linear mixed effects modelling. Results: Of 695 patients admitted, 299 and 226 returned at 3 and 12 months, respectively (median age 59 years, 69% male, 31% severe disease). About half and a third of the patients reported fatigue, dyspnoea and/or cognitive impairment at 3 and 12 months, respectively. Reduced 6MWD and quadriceps strength were present in 20% and 60% at 3 months versus 7% and 30% at 12 months. A high anxiety score and body mass index correlated with poor functional recovery. At 3 months, diffusing capacity for carbon monoxide ( D LCO ) and total lung capacity were below the lower limit of normal in 35% and 18%, decreasing to 21% and 16% at 12 months; predictors of poor D LCO recovery were female sex, pre-existing lung disease, smoking and disease severity. Chest CT improved over time; 10% presented non-progressive fibrotic changes at 1 year. Conclusion: Many COVID-19 survivors, especially those with severe disease, experienced limitations at 3 months. At 1 year, the majority showed improvement to almost complete recovery. To identify additional care or rehabilitation needs, we recommend a timely multidisciplinary follow-up visit following COVID-19 admission. Most hospitalised #COVID19 survivors show promising recovery 1 year after discharge, although mild symptoms may linger. Severe impairments are rare, but this study suggests an evaluation of the individual care needs after discharge. https://bit.ly/3sZK45x